Quality Control of Platelet Concentrates by the Thrombostat 4000 - Böck, Markus; Groh, Joachim; Glaser, Anle; Storck, Klaus; Kratzer, Michael AA; Böck, Markus; Heim, Marcell U. (Seminars in Thrombosis and Hemostasis, 1995)
Quality control of platelet concentrates (PC) is an important prerequisite for good transfusion praxis. However, direct measurement of platelet function is complex, since available methods (e.g. aggregometry, serotonin release) are time consuming and require special equipment. Therefore a test system is needed, which is easy to handle, fast, and achieves reliable results. The present paper compares the results of conventional platelet function tests with those of a modified in-vitro bleeding test (IVBT) (Thrombostat 4000) in liquid-stored and cryopreserved PCs. A high correlation between aggregometry, serotonin release, GMP 140 expression upon stimulation, and IVBT was demonstrated. Therefore IVBT seems to be a good alternative to the conventional platelet function tests for quality control of PCs. In addition, a good correlation between the results of IVBT of patients’ blood after PC transfusion and IVBT of patients blood before transfusion supplemented with platelets of the respective PC could be found. Therefore IVBT seems to be able to predict PC transfusion success. However, since these data were obtained in a small sample undergoing bone marrow transplantation, further studies are needed to verify this hypothesis.
Keywords: platelets; platelet function; Thrombostat; transfusion; bone marrow transplant